The study of visitor satisfaction and intention to revisit in Nilai 3, Negeri Sembilan / Norfazimah Zulkifli, Nur Waie Damia Muhamad Jamil and Nurfarah Ain Mustafa - Zulkifli, Norfazimah; Muhamad Jamil, Nur Waie Damia; Mustafa, Nurfarah Ain (2015)
The objective of this study is to investigate the relationship between customer interaction, convenience, and variety as an antecedent on visitor satisfaction and intention to revisit the destination in Nilai 3, Negeri Sembilan. This study also identified the relationship between the mediator of visitor satisfaction and intention to revisit in Nilai 3, Negeri Sembilan. A total of 300 questionnaires were collected from visitor who had visited the destination. The data is analysed using Statistical Package for Social Sciences System (SPSS). The results of this study indicated that customer interaction has the greatest influence on the visitor satisfaction followed by convenience and variety. Therefore, customer interaction is important to satisfy visitors to return back to Nilai 3 as visitor also shop for social reason.